Strengthening Participant Education and Healthcare Service Delivery through Mobile JKN at BPJS Healt in Bantaeng Regency - Christine Angela Palunsu (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to examine the role of the Mobile JKN application in strengthening healthcare service delivery and participant education within the National Health Insurance system at BPJS Kesehatan Bantaeng Regency, focusing on its function as a digital service innovation and an educational platform for JKN participants. Methodology: This study used a qualitative case study design. Data were collected through in-depth interviews, direct observation, and document review. Informants included BPJS Kesehatan officers and Mobile JKN users, selected purposively. Data analysis applied interactive qualitative analysis techniques, including data reduction, data display, and conclusion drawing. Main Findings: The findings show that Mobile JKN improves healthcare service efficiency, accessibility, and administrative convenience. The application reduces queues and physical visits while providing integrated educational features on JKN procedures, rights, and obligations. However, utilization remains uneven, with lower adoption among elderly participants and those with limited digital literacy and internet access. Novelty/Originality of this study: This study presents an integrative perspective by positioning Mobile JKN as both a healthcare service delivery tool and a participant education medium. It advances existing knowledge by emphasizing education as a core dimension of digital health innovation within a national health insurance system, supported by localized empirical evidence from a regional BPJS context.